ANTIMICROBIAL POTENTIAL AND PRELIMINARY PHYTOCHEMICAL EVALUATION OF CUCURBITA MAXIMA SEEDS - DEVESH KUMAR KUSHAWAHA,; SANJUKTA CHATTERJI,; MANJULIKA YADAV,; GEETA WATAL, (International Journal of Pharma and Bio Sciences, 2016)
In the present study, aqueous extract of Cucurbita maxima seeds was evaluated for its antibacterial activity against five different bacterial strains viz. Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Enterococcous faecalis and Pseudomonas aeruginosa. The susceptibility of bacterial strains against the extract was determined using disc diffusion method. All of the bacterial strains were found to be significantly susceptible against the extract except P. aeruginosa, which was least susceptible showing Zone of Inhibition (ZOI) of 4 mm. However, maximum antibacterial activity of C. maxima seed extract was observed against E. coli and E. faecalis with ZOI of 7 mm. Preliminary phytochemical screening revealed the presence of alkaloids, tannins, saponins, proteins, carbohydrates and glycosides in the extract. The data suggests that C. maxima seed extract could be developed as a promising bactericidal agent for curing several bacterial infections.